1989
DOI: 10.1111/j.1399-302x.1989.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucosyltransferases of Streptococcus sobrinus C211 are both stimulated and inhibited by hydrogen peroxide

Abstract: There are 2 glucosyltransferases (GTF) produced by Streptococcus sobrinus C211. One enzyme, GTF-S, produces a water-soluble glucan that is a-1,6-linked, with short a-1,3 branches, and the other enzyme, GTF-I, produces a water-insoluble glucan that is a-1,3-linked with a-1,6 branches. Hydrogen peroxide was found not only to be a potent inhibitor of GTF activity, but also a stimulator of GTF activity when employed at relatively low concentrations. At 0.88 M, H2O2 completely inhibited insoluble glucan synthesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…1). A similar profile of GTase activities has been obtained ; 38 lower concentrations of hydrogen peroxide stimulated insoluble glucan synthesis of S. sobrinus GTases, whereas higher concentrations of this agent caused complete inhibition of glucan production by GTase-S and GTase-I. This phenomenon may be due to crosslinking of the enzyme proteins through tyrosine residues or deamination of lysyl residues of G T~s~.~~ Some surfactants, e g , cationic or ampholytic, may induce hydrophobic or ionic interactions between GTases and a functional hydrophobic group within the surfactant molecule.…”
Section: Discussionmentioning
confidence: 57%
“…1). A similar profile of GTase activities has been obtained ; 38 lower concentrations of hydrogen peroxide stimulated insoluble glucan synthesis of S. sobrinus GTases, whereas higher concentrations of this agent caused complete inhibition of glucan production by GTase-S and GTase-I. This phenomenon may be due to crosslinking of the enzyme proteins through tyrosine residues or deamination of lysyl residues of G T~s~.~~ Some surfactants, e g , cationic or ampholytic, may induce hydrophobic or ionic interactions between GTases and a functional hydrophobic group within the surfactant molecule.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, hydrogen peroxide has previously been shown to be bactericidal for oral micro-organisms (Wennstrom et al, 1979;Thomas et al, 1983). It was observed that high concentrations of hydrogen peroxide may be inhibitory to GTF and oral microbes, but low concentrations may actually enhance caries activity due to the increase in production of insoluble glucans that mediate attachment of S. mutans to smooth surfaces (McAlister et al, 1989). The present study involves Fenton chemistry, which is often cited as a model for biological processes such as in vivo oxidative damage occurring during certain disease states, carcinogenesis, and drug-associated toxicity (Ames et al, 1981;Gutteridge, 1984, 1986;Aust et al, 1985;Wink et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the interactions between the enzymes were lost after LP was bound with its substrates. Although H 2 O 2 alone has some inhibitory effect on Gtfs from Streptococcus sobrinus [McAlister et al, 1989], concentrations used in our study were not effective. As SCN -was also ineffective, it is unlikely that minor changes in the ionic strength of the medium were responsible for loss of the inhibition and enhancements of Gtf activity.…”
Section: Discussionmentioning
confidence: 43%